The Importance of Knowledge in Improving Healthcare Services (Comprehensive Journal of Science, 2026)
This study aimed to examine the impact of knowledge management capabilities on improving the quality of healthcare services in primary healthcare centers in Qasr Bin Ghashir Municipality. Knowledge management capabilities were conceptualized through two main dimensions: infrastructure capabilities (organizational structure, organizational culture, and technology) and process capabilities (knowledge acquisition, knowledge dissemination, and knowledge responsiveness). The study adopted a descriptive-analytical approach. Data were collected באמצעות a structured questionnaire distributed to a stratified random sample of 640 employees and clients, of which 540 valid responses were analyzed using SPSS.The findings revealed a statistically significant positive effect of knowledge management capabilities on the quality of healthcare services across its five dimensions (tangibility, reliability, responsiveness, empathy, and assurance). Organizational culture and knowledge dissemination were identified as the most influential factors in enhancing service quality. The results also indicated that the overall level of knowledge management capabilities and healthcare service quality was moderate, highlighting the need to strengthen knowledge infrastructure and activate knowledge processes within healthcare centers.The study recommends developing health information systems, fostering a supportive organizational culture that encourages knowledge sharing, and improving responsiveness mechanisms to patients’ needs in order to enhance healthcare service quality and achieve organizational excellence.
Keywords: Knowledge Management, Knowledge Management Capabilities, Healthcare Service Quality, Primary Healthcare Centers, Libya